2019
DOI: 10.1155/2019/2053958
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine and Cytokine Cascade Caused by Skewing of the Th1-Th2 Balance Is Associated with High Intracranial Pressure in HIV-Associated Cryptococcal Meningitis

Abstract: Purpose. Serum cytokines/chemokines play important roles in cryptococcal meningitis, but it is unclear whether cytokines/chemokines in cerebrospinal fluid (CSF) contribute to high intracranial pressure (HICP) in HIV-associated cryptococcal meningitis (HCM). Methods. CSF cytokines/chemokines were assayed in 17 HIV-uninfected patients, 26 HIV-infected patients without CNS infection, and 39 HCM patients at admission. Principal component analysis and correlation and logistic regression analyses were used to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Our present study was coincident with our previous study, showing that Th1 cytokines (IL-12p70, TNF-β and TNF-α), Th2 cytokines (IL-5) and CD40L together contribute to HCM [11]. Th1 cytokine expression is an immune response to Cryptococcus infection and an over-response of Th1 cytokines is associated with extensive inflammation in Cryptococcus infection [22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our present study was coincident with our previous study, showing that Th1 cytokines (IL-12p70, TNF-β and TNF-α), Th2 cytokines (IL-5) and CD40L together contribute to HCM [11]. Th1 cytokine expression is an immune response to Cryptococcus infection and an over-response of Th1 cytokines is associated with extensive inflammation in Cryptococcus infection [22].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the CSF cytokine profiles predicted immune reconstitution inflammatory syndrome (IRIS) and even mortality in HCM patients [4]. Our study also showed that chemokine and cytokine cascades caused by the skewing of the T helper type (Th)1–Th2 balance are associated with severity in HCM patients [11]. Inflammatory mediators in the CSF are attracting increasing attention, and play a critical role in HTBM [12].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Cryptococcus spp. Isolates (8,14,(34)(35)(36)(37)(38). Genetic and environmental factors contribute to the variation in the melanin production of C. neoformans (39,40), which is under complex cellular regulation (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…On the opposite, Th2 cytokines act as down-regulators of the cellular immune response, inhibit T cell proliferation and are associated with impaired infection control and poor prognosis [ 15 , 24 ]. Xu et al found that [ 25 ], HIV + CM+ patients had higher levels of CSF cytokines and chemokines than HIV-CM- patients, Th1 cytokines (such as TNF-α, IFN-γ and IL-12), Th2 cytokines (such as IL-4, IL-5, IL-6 and IL-12) and macrophage cytokines (such as IL-8 and CCL2) were particular high indicated the unbalance of Th1-Th2 cytokines in CSF. Most of our results were consistent with the previous study, but we found IL-4 in CSF of HIV + CM+ patients were lower than that of HIV-CM- patients.…”
Section: Discussionmentioning
confidence: 99%